Isolasi dan Seleksi Jamur Perusak Karet dari Berbagai Sumber Kontaminasi Potensial - Maria Ulfah; Purnomo Darmadji; Retno Indrati (agriTECH, 2001)
Ribbed smoked sheet (RSS) is Natural rubber product, mainly consist of Cis- 1,4 polyisoprene and relatively resistant to microbial decomposition with many other natural polymer. Natural rubber contains a minimum of 90% rubber hydrocarbon, plus small amounts of protein, resins, fatty acid, sugars and minerals. It is also possible that microorganisms using impurities as their carbon and energy sources could deteoriorate the rubber. Fungi which potentially deteriorate rubber eventually was accidentally taken by raw material areas, raw materials, processing steps, product and old RSS. Therefore it is necessary to isolate fungi and to evaluate potential fungi which deteriorated rubber. The results showed that 158 strains were isolated from various contaminant sources. From these 10 strains were from skin of rubber wood, 7 strains from tappinglump, 16 strains from spoutlump and 10 strains from cuplump, 47 strains from earth around rubber wood, 5 strains from fresh field latex, 3 strains from ammoniated field latex, 12 strains from wet sheet, 7 strains from air in wet in sorting room, 12 strains from RSS product, 11 strains from old RSS product (7 years old namely SU) and 8 strains from wet SU (1 month old namely SDU) Twenty four strains were selected as potential deteriorated rubber fungi. These 24 strains were classified into 10 genera (Aspergillus, Cladosporium, Emericella, Fusarium, Mucor, Neosartorya, Penicillium, Pestalotiopsis, Cladobotyrum, Pithomyces), and 4 unidentified strains (LM188, T55, SS37, T67).